Impact Evaluation of the Human Resource for Health Deployment Program (HRHDP) - Michael Ralph M. Abrigo; Gina A. Opiniano; Zhandra C. Tam (Philippine Institute for Development Studies (PIDS), 2023)
We assess the short-term impacts of the Doctors-to-the-Barrios (DTTB), a national physician deployment program in the Philippines that augments the supply of rural healthcare workers in underserved areas, on several health sector outcomes. Using regression discontinuity design, we find that the DTTB program doubles modern contraceptives-use prevalence and reduces child underweight prevalence in poor municipalities, coinciding with increased propensity of having rural health physicians in the community. We estimated a program internal rate of return of 15.9%, which is likely to be severely understated.
Keywords: 330; rural health physician; doctors-to-the-barrios program; maternal and child health